TINDAK TUTUR TIDAK LANGSUNG PADA SERIAL DRAMA NIHONJIN NO SHIRANAI NIHONGO - Tari Kencana Erly; Ratmanida Ratmanida; Zalman Hendri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2018)
This research is motivated by speech act that are very necessary to communicate in everyday life. Speech act must be spoken with regard to when, where, and with whom someone speaks so as not to offend the other person, knowing that indirect directive speech acts are expected to avoid misunderstandings in talking to the other person. This study aims to describe the mode and meaning of indirect directive speech act on the Nihonjin no Shiranai Nihongo drama series. This study uses mode and meaning theory. This type of research is descriptive research, which produces data in the form of words and numbers. This research was carried out by the following steps: (1) classifying the mode and meaning of the indirect directive speech act in the conversation in the Nihonjin no Shiranai Nihongo drama series according to the data instrument, (2) classifying data according to mode and meaning theory.Keywords : directive speech act, indirect speech act, mode, meaningNihonjin no Shiranai Nihongo drama series according to the data instrument, (2) classifying data according to mode and meaning theory . Keywords: directive speech act, indirect speech act, mode, meaning